Optimal Convergence Rates of Moving Finite Element Methods for Space-Time Fractional Differential Equations - Xuemei Gao; Xu Han (Journal of Applied Mathematics)
This paper studies the moving finite element methods for the space-time fractional differential equations. An optimal convergence rate of the moving finite element method is proved for the space-time fractional differential equations.